Studying Summer Season Drought in Western Russia - Anthony R. Lupo; Igor I. Mokhov; Yury G. Chendev; Maria G. Lebedeva; Mirseid Akperov; Jason A. Hubbart (Advances in Meteorology)
During the 2010 summer, a severe drought impacted Western Russia, including regions surrounding Moscow and Belgorod (about 700 km south of Moscow). The drought was accompanied by high temperatures. Moscow recorded 37.8°C (100°F) for the first time in over 130 years of record keeping. The record heat, high humidity, dry weather, and smoke from forest fires caused increased human mortality rates in the Moscow region during the summer. The excessive heat and humidity in Western Russia were the result of atmospheric blocking from June through mid-August. The NCAR-NCEP reanalyses were used to examine blocking in the Eastern European and Western Russia sector during the spring and summer seasons from 1970 to 2012. We found that drier years were correlated with stronger and more persistent blocking during the spring and summer seasons. During these years, the Moscow region was drier in the summer and Belgorod during the spring seasons. In the Moscow region, the drier summers were correlated with transitions from El Niño to La Niña, but the opposite was true in the Belgorod region. Synoptic flow regimes were then analyzed and support the contention that dry years are associated with more blocking and El Niño transitions.